Exploring the Multifunctionality of Mechanochemically Synthesized γ-Alumina with Incorporated Selected Metal Oxide Species - Rabindra Dubadi; Ewelina Weidner; Bogdan Samojeden; Teofil Jesionowski; Filip Ciesielczyk; Songping Huang; Mietek Jaroniec (Molecules, 2023)
γ-Alumina with incorporated metal oxide species (including Fe, Cu, Zn, Bi, and Ga) was synthesized by liquid-assisted grinding—mechanochemical synthesis, applying boehmite as the alumina precursor and suitable metal salts. Various contents of metal elements (5 wt.%, 10 wt.%, and 20 wt.%) were used to tune the composition of the resulting hybrid materials. The different milling time was tested to find the most suitable procedure that allowed the preparation of porous alumina incorporated with selected metal oxide species. The block copolymer, Pluronic P123, was used as a pore-generating agent. Commercial γ−alumina (SBET = 96 m2·g−1), and the sample fabricated after two hours of initial grinding of boehmite (SBET = 266 m2·g−1), were used as references. Analysis of another sample of γ-alumina prepared within 3 h of one-pot milling revealed a higher surface area (SBET = 320 m2·g−1) that did not increase with a further increase in the milling time. So, three hours of grinding time were set as optimal for this material. The synthesized samples were characterized by low-temperature N2 sorption, TGA/DTG, XRD, TEM, EDX, elemental mapping, and XRF techniques. The higher loading of metal oxide into the alumina structure was confirmed by the higher intensity of the XRF peaks. Samples synthesized with the lowest metal oxide content (5 wt.%) were tested for selective catalytic reduction of NO with NH3 (NH3-SCR). Among all tested samples, besides pristine Al2O3 and alumina incorporated with gallium oxide, the increase in reaction temperature accelerated the NO conversion. The highest NO conversion rate was observed for Fe2O3-incorporated alumina (70%) at 450 °C and CuO-incorporated alumina (71%) at 300 °C. The CO2 capture was also studied for synthesized samples and the sample of alumina with incorporated Bi2O3 (10 wt.%) gave the best result (1.16 mmol·g−1) at 25 °C, while alumina alone could adsorb only 0.85 mmol·g−1 of CO2. Furthermore, the synthesized samples were tested for antimicrobial properties and found to be quite active against Gram-negative bacteria, P. aeruginosa (PA). The measured Minimum Inhibitory Concentration (MIC) values for the alumina samples with incorporated Fe, Cu, and Bi oxide (10 wt.%) were found to be 4 µg·mL−1, while 8 µg·mL−1 was obtained for pure alumina.